(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
In our initial paper discussing plausible steps toward workable warp drive machines. The following article express our view on this debate. While there are still objections toward existing warp drive proposals, such as by G. Landis, Harold White etc., because they are all based on GTR, nonetheless we think it is possible by starting to see if it is possible to deviate from Newton’s third law. And we discuss possible a propulsion method based on negative masses, and discuss how optical diameter drive can be first step for realistic lab-scale version of negative mass propulsion.